A novel mouse model of trauma induced heterotopic ossification. Issue 2 (17th October 2013) - Liu, Xuhui; Kang, Heejae; Shahnazari, Mohammad; Kim, Hubert; Wang, Liping; Larm, Olla; Adolfsson, Lars; Nissenson, Robert; Halloran, Bernard
Abstract Severe soft tissue trauma is associated with heterotopic ossification (HO), the abnormal deposition of bone at extra‐skeletal sites. The pathophysiology of the development of trauma‐induced HO remains largely unknown due in part to the lack of appropriate animal models. In this study, we sought to develop a new trauma‐induced HO mouse model using muscle impact injury combined with low dose BMP‐2. BMP‐2 at doses ranging from 0 to 2 µg was injected into quadriceps muscles of adult male C57/BL6 mice. Animals then received a one‐time quadriceps impaction injury to mimic the trauma associated with severe injuries. HO was monitored using in vivo microCT scanning at 1, 2, 4, and 8 weeks after treatment. After trauma, the expression of BMP‐2, ‐4, BMP receptor 1, SOX9 and RUNX2 were increased in muscle. Although little or no HO was observed in mice receiving 1 µg BMP‐2, combining this dose with muscle trauma produced an abundance of HO. At higher doses of BMP‐2, trauma did not augment mineral deposition. These results suggest that BMP‐2 signaling can sensitize muscle to trauma‐induced HO. They also provide the basis for a new model to study the pathogenesis of trauma‐induced HO. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:183–188, 2014.